Synchrotron radiation based X-ray techniques for analysis of cathodes in Li rechargeable batteries - Singh, Jitendra Pal; Paidi, Anil Kumar; Chae, Keun Hwa; Lee, Sangsul; Ahn, Docheon (Royal Society of Chemistry, 2022)
Li-ion rechargeable batteries are promising systems for large-scale energy storage solutions. Understanding the electrochemical process in the cathodes of these batteries using suitable techniques is one of the crucial steps for developing them as next-generation energy storage devices. Due to the broad energy range, synchrotron X-ray techniques provide a better option for characterizing the cathodes compared to the conventional laboratory-scale characterization instruments. This work gives an overview of various synchrotron radiation techniques for analyzing cathodes of Li-rechargeable batteries by depicting instrumental details of X-ray diffraction, X-ray absorption spectroscopy, X-ray imaging, and X-ray near-edge fine structure-imaging. Analysis and simulation procedures to get appropriate information of structural order, local electronic/atomic structure, chemical phase mapping and pores in cathodes are discussed by taking examples of various cathode materials. Applications of these synchrotron techniques are also explored to investigate oxidation state, metal-oxygen hybridization, quantitative local atomic structure, Ni oxidation phase and pore distribution in Ni-rich layered oxide cathodes.